Optoacoustic imaging identifies ovarian cancer using a microenvironment targeted theranostic wormhole mesoporous silica nanoparticle. (November 2018) - Samykutty, Abhilash; Grizzle, William E.; Fouts, Benjamin L.; McNally, Molly W.; Chuong, Phillip; Thomas, Alexandra; Chiba, Akiko; Otali, Dennis; Woloszynska, Anna; Said, Neveen; Frederick, Peter J.; Jasinski, Jacek; et al.
Abstract: At the intersection of the newly emerging fields of optoacoustic imaging and theranostic nanomedicine, promising clinical progress can be made in dismal prognosis of ovarian cancer. An acidic pH targeted wormhole mesoporous silica nanoparticle (V7-RUBY) was developed to serve as a novel tumor specific theranostic nanoparticle detectable using multispectral optoacoustic tomographic (MSOT) imaging. We report the synthesis of a small, < 40 nm, biocompatible asymmetric wormhole pore mesoporous silica core particle that has both large loading capacity and favorable release kinetics combined with tumor-specific targeting and gatekeeping. V7-RUBY exploits the acidic tumor microenvironment for tumor-specific targeting and tumor-specific release. In vitro, treatment with V7-RUBY containing either paclitaxel or carboplatin resulted in increased cell death at pH 6.6 in comparison to drug alone (p < 0.0001). In orthotopic ovarian xenograft mouse models, V7-RUBY containing IR780 was specifically detected within the tumor 7X and 4X higher than the liver and >10X higher than in the kidney using both multispectral optoacoustic tomography (MSOT) imaging with secondary confirmation using near infrared fluorescence imaging (p < 0.0004). The V7-RUBY system carrying a cargo of either contrast agent or an anti-neoplastic drug has the potential to become a theranostic nanoparticle which can improve both diagnosis and treatment of ovarian cancer.